Observation of high dielectric constants in x (Pb (Zn13 Nb23) O3 - (0.2-x) Pb (Ni13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 ternary solid solutions - Nabunmee, Sucheewan; Rujijanagul, Gobwute; Vittayakorn, Naratip; Cann, David P. (My University, 2007)
In the present work, we demonstrate the results of combining two excellent ferroelectric materials at their morphotropic phase boundary compositions, i.e., 0.2 (Pb (Zn13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 (0.2PZN-0.8PZT) and 0.2Pb (Ni13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 (0.2PNN-0.8PZT) to form a ternary solid solution of x (Pb (Zn13 Nb23) O3 - (0.2-x) Pb (Ni13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 (xPZN- (0.2-x) PNN-0.8PZT) which exhibits superior dielectric properties. Examination of the dielectric spectra indicated that the ternary system exhibits a very high relative permittivity of 49 800 (at 10 kHz) for the composition at x=0.10. In addition, an increased amount of PZN was observed to enhance the ferroelectric properties of the system. © 2007 American Institute of Physics.